A Review on Understanding the Connecting link between Genes and Cancer and the Involvement of Genetics in Cancer Development - Ishani Saha; Jutishna Bora (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Cancer genetics is the scientific discipline that investigates the genes and pathways that drive the development of cancer. Cancer geneticists use several approaches including the analysis of the genomes of cancer patients, and that of their tumors, to identify cancer genes. These studies are performed along with experiments in in vitro and in vivo models to decipher the mechanisms that drive tumorigenesis. Cancer geneticists aim to identify cancer genes, that when mutated, contribute towards cancer development by promoting tumor cell growth and by conferring upon a neoplastic cell the ability to evade the cell cycle and apoptosis checkpoints that might normally control their growth. Cancer geneticists are also interested in the networks and pathways that contribute to tumor development and the way cancer genes work together to market tumor evolution.